Job Design and Innovative Work Behavior: One Size Does Not Fit All Types of Employees - Stan De Spiegelaere; Geert Van Hootegem; Guy Van Gyes (Journal of Entrepreneurship, Management and Innovation)

(untitled)
As innovative employees become imperative for an organizations’ success, research identified job design as a crucial variable in promoting innovative work behavior (IWB) (Hammond et al., 2011). Using the Job Demands-Resources (JD-R) model of Bakker & Demerouti (2007), this article contributes to the literature as it uses recent insights on the distinction between job challenges and job hindrances (Van den Broeck et al., 2010) and distinguishes between blue- and white-collar employees. Using survey data of 893 employees of various organizations the findings generally confirm the JD-R model, although important differences were found between blue-collar and white-collar employees regarding the relation of organizing and routine tasks with IWB. Job content insecurity further was found to be very detrimental for blue-collar IWB. These findings have important HR and political implications as they show that there is no ‘one size fits all’ HR solution for innovation.